Foam metal catalysts with intermediate support for deep oxidation of hydrocarbons; Reaction kinetics and catalysis letters; Vol. 53, № 2 - Pestryakov A. N. Aleksey Nikolaevich (1994, 1994)
Catalytic and gas-dynamic properties of block catalysts with a cellular structure (foam metals) have been investigated. Foam metal catalysts with intermediate support AI203 have high catalytic activity, gas permeability and mechanical strength.